2020
DOI: 10.14444/7116
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons' Learning Curve of Renaissance Robotic Surgical System

Abstract: Introduction: A few articles on robot-assisted pedicle screw placement described the learning curve but failed to report on the overall operative time, including cases in which the robotic system malfunctioned. The purpose of this study was to identify a single surgeon's learning curve including estimated blood loss, surgery time, anesthesia time, robot time, and complications. Methods: A retrospective study was performed between January 2016 and August 2018 for patients who underwent posterior spinal fusion u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…A significant improvement in estimated intraoperative blood loss was observed with a decrease in time in anesthesia, surgery, and robotic usage as well as a decrease in pedicle screw-insertion time and operative time [13]. The complication rate did not show any learning curve [13]. Technical issues such as registration and installation issues, a software bug and a placement issue have been described [13].…”
Section: Disadvantages Of Robotic-guided Spine Surgerymentioning
confidence: 96%
See 3 more Smart Citations
“…A significant improvement in estimated intraoperative blood loss was observed with a decrease in time in anesthesia, surgery, and robotic usage as well as a decrease in pedicle screw-insertion time and operative time [13]. The complication rate did not show any learning curve [13]. Technical issues such as registration and installation issues, a software bug and a placement issue have been described [13].…”
Section: Disadvantages Of Robotic-guided Spine Surgerymentioning
confidence: 96%
“…Lonjon et al found a significantly longer mean operative time in the robotic cohort than the freehand cohort, and attributed this increased time to both the learning curve and set-uptime for robotic use [53]. A significant improvement in estimated intraoperative blood loss was observed with a decrease in time in anesthesia, surgery, and robotic usage as well as a decrease in pedicle screw-insertion time and operative time [13]. The complication rate did not show any learning curve [13].…”
Section: Disadvantages Of Robotic-guided Spine Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…There was no difference in operative times between the initial adoption phase and later periods, which would imply a negligible learning curve at best [7]. Bäcker et al found that overall procedural times decreased as more robotic-assisted procedures were performed but also concluded that there was no major learning curve for the technology [2]. Interestingly, Urakov et al examined robotic surgeries and identified a trend toward improved efficiency with pedicle screw placement over time, although no statistically significant pattern was discovered [14].…”
Section: The Learning Curvementioning
confidence: 99%